2018
DOI: 10.3892/ol.2018.8371
|View full text |Cite
|
Sign up to set email alerts
|

HOXB13 expression and promoter methylation as a candidate biomarker in gastric cancer

Abstract: Homeobox b13 (HOXB13) is considered to be a tumor suppressor gene in multiple types of human cancer. The present study aimed to identify the difference in expression of HOXB13 mRNA between gastric cancer (GC) tissues and corresponding non-malignant gastric tissues. The clinical significance of HOXB13 mRNA expression was also assessed in GC and a potential association between HOXB13 mRNA expression and DNA promoter methylation was observed. The expression of HOXB13 mRNA was assessed by reverse transcription-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…The role of HOXB13 tumor suppressor has been also demonstrated in gastric cancer [114] in which HOXB13 mRNA is significantly lower in primary tumors and its de-regulation is associated with a poorer differentiation, lymph node metastases, invasion and TNM stage. HOX B13 expression is increased by the treatment of GC cells with DNA methyltransferase inhibitor 5-aza-dC[115]. In HCC patients, aberrant expression of HOXB13 is strongly associated with clinic-pathological features, such as vascular invasion, tumor grade, TNM stage and a poorer survival.…”
Section: Hoxb13mentioning
confidence: 99%
“…The role of HOXB13 tumor suppressor has been also demonstrated in gastric cancer [114] in which HOXB13 mRNA is significantly lower in primary tumors and its de-regulation is associated with a poorer differentiation, lymph node metastases, invasion and TNM stage. HOX B13 expression is increased by the treatment of GC cells with DNA methyltransferase inhibitor 5-aza-dC[115]. In HCC patients, aberrant expression of HOXB13 is strongly associated with clinic-pathological features, such as vascular invasion, tumor grade, TNM stage and a poorer survival.…”
Section: Hoxb13mentioning
confidence: 99%
“…14 Low HOXB13 expression is a poor prognostic factor in patients with gastric cancer. 15 Compared with its expression in normal colon tissue, HOXB13 expression in colorectal cancer (CRC) is downregulated, a common event in cancer progression. 16,17 A study based on tumor gene expression data showed that several homeobox genes are related to tumor location.…”
Section: Introductionmentioning
confidence: 99%
“…The genes marked in * bold in Table 2 and in Table S3 are those that met these 2 criteria. These genes were already suggested for consideration as prognostic biomarkers in previous studies (selected references are listed in Table S12 [ 34 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]).…”
Section: Discussionmentioning
confidence: 99%